DNA methylation of the filaggrin gene adds to the risk of eczema associated with loss‐of‐function variants. (25th September 2012) - Ziyab, A.H.; Karmaus, W.; Holloway, J.W.; Zhang, H; Ewart, S.; Arshad, S.H.
Abstract Background Loss‐of‐function variants within the filaggrin gene (FLG) are associated with a dysfunctional skin barrier that contributes to the development of eczema. Epigenetic modifications, such as DNA methylation, are genetic regulatory mechanisms that modulate gene expression without changing the DNA sequence. Objectives To investigate whether genetic variants and adjacent differential DNA methylation within the FLG gene synergistically act on the development of eczema. Methods A subsample (n = 245, only females aged 18 years) of the Isle of Wight birth cohort participants (n = 1456) had available information for FLG variants R501X, 2282del4 and S3247X and DNA methylation levels for 10 CpG sites within the FLG gene. Log‐binomial regression was used to estimate the risk ratios (RRs) of eczema associated with FLG variants at different methylation levels. Results The period prevalence of eczema was 15.2% at age 18 years and 9.0% of participants were carriers (heterozygous) of FLG variants. Of the 10 CpG sites spanning the genomic region of FLG, methylation levels of CpG site 'cg07548383' showed a significant interaction with FLG sequence variants on the risk for eczema. At 86% methylation level, filaggrin haploinsufficient individuals had a 5.48‐fold increased risk of eczema when compared to those with wild type FLG genotype (P‐value = 0.0008). Conclusions Our novel results indicated that the association between FLG loss‐of‐function variants and eczema is modulated by DNA methylation. Simultaneously assessing the joint effect of genetic and epigenetic factors within the FLG gene further highlights the importance of this genomic region for eczema manifestation.